Implementasi Evaluasi Pembelajaran Fiqih dalam Mengoptimalkan Hasil Belajar Siswa di MTs N 2 Pamekasan - Salistya Irfani; Masna Nurfadilah; Abd. Mukhid (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
This research is motivated by the importance of learning evaluation in Islamic education, particularly in the subject of Islamic jurisprudence (fiqh), which emphasizes not only cognitive aspects but also affective and psychomotor aspects. To date, evaluation has often not been optimally utilized as a means of improving student learning outcomes. Therefore, this study aims to describe the implementation of formative and summative assessments and analyze their role in optimizing student learning outcomes at MTsN 2 Pamekasan. The method used is qualitative research with a descriptive approach. The research subjects included the principal and fiqh teachers who were selected purposively. Data collection techniques were carried out through interviews, observation, and documentation, then analyzed using data reduction, data presentation, and drawing conclusions with triangulation to maintain data validity. The results show that the evaluation of fiqh learning has been systematically designed, implemented continuously through formative and summative assessments, and uses varied and authentic assessment techniques. This evaluation has been proven to improve student learning outcomes, both from the cognitive, affective, and psychomotor aspects, as well as shaping students' character and religious practice skills more optimally.